2019
DOI: 10.1111/pde.13775
|View full text |Cite
|
Sign up to set email alerts
|

Combination hyperbaric oxygen therapy and ustekinumab for severe hidradenitis suppurativa

Abstract: Hidradenitis suppurativa is a painful chronic inflammatory skin condition characterized by inflammatory nodules that can lead to sinus tracts and scarring. Numerous treatments have been reported, though none have reliable efficacy. Anti inflammatory agents, such as tumor necrosis factor-alpha inhibitors and interleukin inhibitors, have been used as medical therapy for refractory cases. We describe here a case of severe hidradenitis suppurativa in a pediatric patient successfully treated with a combination of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
(5 reference statements)
0
15
0
Order By: Relevance
“…In cases where the pretest probability of IBD is high, a normal FCP value is unlikely to prevent an endoscopy. For example, in a child with hidradenitis suppurativa, low albumin and perianal fistula, a normal FCP test did not preclude further investigation, and an endoscopy and biopsy were subsequently performed to exclude IBD 24 . In such cases, the value of FCP is debatable.…”
Section: Faecal Calprotectin Testing In Dermatologymentioning
confidence: 99%
“…In cases where the pretest probability of IBD is high, a normal FCP value is unlikely to prevent an endoscopy. For example, in a child with hidradenitis suppurativa, low albumin and perianal fistula, a normal FCP test did not preclude further investigation, and an endoscopy and biopsy were subsequently performed to exclude IBD 24 . In such cases, the value of FCP is debatable.…”
Section: Faecal Calprotectin Testing In Dermatologymentioning
confidence: 99%
“…In total, 15 studies met eligibility criteria and were used for data collection and analysis of 26 patients. 13 - 27 The analysis of the level of evidence showed that 6 studies (40%) had a level of evidence of 4 and 9 studies (60%) had a level of evidence of 5. Overall, patients were between 6 and 17 years of age (mean: 15 years ± 2.3) at presentation and initiation of biologics.…”
Section: Resultsmentioning
confidence: 99%
“…6 However, this study reviewed mostly adult patients and did not report pediatric data separately, 6 whereas our review included only pediatric studies. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In addition to anti-TNF-α , anti-IL-1 may be effective against HS as elevated TNF-α and IL-1β levels have been detected in HS lesions. 28 IL-1β and TNF-α levels in HS lesions were elevated 31-fold and 5-fold, compared to healthy skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, according to the authors’ experience, the long-term efficacy of secukinumab may not be influenced by the administration or not of induction [ 245 ]. A successful combination of hyperbaric oxygen therapy (6 days per week for 6 weeks) and high-dose ustekinumab (90 mg every 4 weeks) was described in a pediatric obese female HS patient [ 246 ].…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 99%